The Impact of Scene Teaching in Smart Classrooms on Learners’ Learning Performance and Effectiveness - Liu, Xin; Wang, Jin (International Journal of Emerging Technologies in Learning (iJET), 2023)
As a new teaching method, scene teaching in smart classrooms directly impacts the overall quality and efficiency of education. Two groups of first-year students were selected as the research subjects for a study on intelligent learning performance and outcomes in a smart classroom teaching scenario. The results indicate that the intelligent teaching mode can lead to better outcomes in learners’ intelligent learning. It can improve learners’ participation in intelligent learning and enhance their performance. Additionally, it highlights the significance and differences in learners’ intelligent learning effects. However, the research process must prioritize the dominant role of students and teachers in teaching in smart classroom settings. It should also focus on upgrading software and hardware to enhance effective teaching and on the rational use of multimedia technology in smart classrooms to provide robust support for college students’ intelligent learning.